2013
DOI: 10.1007/s13762-013-0285-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irrigation with olive mill wastewater on soil hydraulic and solute transport properties

Abstract: To evaluate the effect of olive mill wastewater (OMW) application on soil hydraulic and transport properties, two treatment sites, which had been irrigated with OMW for 5 and 15 years, and one control site being irrigated with freshwater were compared. The transport and leaching experiment results showed that a portion of the total soil water was available for transport processes while the remaining of the soil water was considered immobile and not readily accessible for solutes. The separation in water fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…With increasing industrialization, environmental problems such as the pollution of the petroleum and saline-alkali fields have become a global issue (Mohawesh et al 2014;Ogri 2001;Sakai et al 2004;Sharma et al 2012). Many developing countries face serious problems with soil pollution, but environmental concerns seem to be a luxury given the economic situation in most countries (Navabakhsh and Tamiz 2013).…”
Section: Introductionmentioning
confidence: 99%
“…With increasing industrialization, environmental problems such as the pollution of the petroleum and saline-alkali fields have become a global issue (Mohawesh et al 2014;Ogri 2001;Sakai et al 2004;Sharma et al 2012). Many developing countries face serious problems with soil pollution, but environmental concerns seem to be a luxury given the economic situation in most countries (Navabakhsh and Tamiz 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, irrigation accounts for 69% of the 3240 km 3 of water withdrawn for human use, and 87% of all water consumed (Gleik 2000). To sustain the rapidly growing world population, agricultural production should be increased (Howell 2001), so far the share of fresh water available for agriculture (72%) is decreasing (Cai & Rosegrant 2003;Mohawesh 2011;Mohawesh et al 2013). Consequently, sustainable methods to increase crop-water productivity are gaining higher value in arid and semi-arid regions (Debaeke & Aboudrare 2004;Mahadeen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…OMW is a primary waste product of olive oil processing. In several countries where olive oil production is very intensive, OMW is often recycled as a low-cost fertilizer, since OMW is naturally rich in mineral elements (Kavvadias et al 2014;Mohawesh et al 2014;Chatzistathis and Koutsos, 2017;Mekki et al, 2018;Chehab et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…From a hydrological standpoint, several studies have shown that high concentrations of suspended solids, organic matter, potassium (K) and sodium (Na) in OMW have the potential to reduce the saturated soil hydraulic conductivity (Mohawesh et al 2014;Regni et al, 2017). Furthermore, lipidic constituents (i.e.…”
Section: Introductionmentioning
confidence: 99%